2020
DOI: 10.1016/j.celrep.2020.108448
|View full text |Cite
|
Sign up to set email alerts
|

Circulating miRNA Spaceflight Signature Reveals Targets for Countermeasure Development

Abstract: Highlights d Spaceflight miRNA signature validated in multiple organism models d Components of miRNA signature related to space radiation and microgravity d Downstream targets and circulating dependence of miRNAs in NASA Twins Study d Inhibition of key microvasculature miRNAs mitigates space radiation impact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 88 publications
1
81
0
Order By: Relevance
“…Together, these data suggest that HIF1A expression differs among tissues/cells, and more importantly, it is modulated by hypoxia-independent pathways. Microgravity and its analogs cause comprehensive physiological changes including autonomic imbalances, cardiac atrophy, vascular impairment and microcirculatory dysfunction, which account for cardiovascular deconditioning [49][50][51]. In this work, we revealed that several pathways involving genes showing altered rhythmicities are associated with cardiovascular deconditioning (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Together, these data suggest that HIF1A expression differs among tissues/cells, and more importantly, it is modulated by hypoxia-independent pathways. Microgravity and its analogs cause comprehensive physiological changes including autonomic imbalances, cardiac atrophy, vascular impairment and microcirculatory dysfunction, which account for cardiovascular deconditioning [49][50][51]. In this work, we revealed that several pathways involving genes showing altered rhythmicities are associated with cardiovascular deconditioning (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Profiling miRNA expression during spaceflight has identified several miRNAs that have key regulatory roles in the cellular response to space [ 72 ]. In a recent study, Malkani et al exposed mice to spaceflight-associated conditions to evaluate the expression of known miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are small single strand non-coding RNA, whose functions in RNA silencing and post-transcriptional regulation of gene expression are well known. A recent milestone study identified a spaceflight-associated microRNA signature in response to simulated, shortduration and long-duration spaceflight, and simulated deep space radiation conditions [78]. In addition, the panel of spaceflight-associated microRNA has been predicted to interfere with cell signaling and metabolic pathways, partly through interaction with TGF-beta signaling [59].…”
Section: Discussionmentioning
confidence: 99%